Nanoarchitectures based on multi-walled carbon nanotubes non-covalently functionalized with Concanavalin A: A new building-block with supramolecular recognition properties for the development of electrochemical biosensors - Ortiz, Elvis (2019)
We propose an innovative nanoarchitecture for the development of electrochemical biosensors based on the non-covalent functionalization of multi-walled carbon nanotubes (MWCNTs) with the lectin Concanavalin A (ConA) and the site-specific supramolecular binding of glycobiomolecules. As proof-of-concept, we propose the use of two glycoenzymes, glucose oxidase (GOx) and horseradish peroxidase (HRP), for building mono and bienzymatic glucose biosensors. The selected conditions for the preparation of the dispersion were 1.5 mg MWCNTs in 1.0 mL of 2.0 mg mL −1 ConA sonicated for 5.0 min with sonicator probe. The monoenzymatic glucose biosensor was prepared by casting GCE with the MWCNTs-ConA dispersion (GCE/MWCNTs-ConA) followed by the interaction with GOx (GCE/MWCNTs-ConA/GOx), while the bienzymatic one was obtained by interaction of GCE/MWCNTs-ConA with GOx + HRP (GCE/MWCNTs-ConA/GOx-HRP). The best analytical performance was obtained with the bienzymatic biosensor from the amperometric response at -0.050 V in the presence of 1.0 × 10 -4 M hydroquinone. The sensitivity was (2.22 ± 0.03) μA mM −1 (which was 5.2 times higher than the one obtained with the monoenzymatic biosensor) and a detection limit of 0.31 μM. The reproducibility was 5.4% and the biosensor was challenged with human blood serum showing an excellent correlation with the values reported by the laboratory.